Modelling the Impact of Financial Attitudes and Social Media on Stock Investment Decisions: The Moderating Role of Risk Preference (Case Study on Macassar City) - Widya, Widya Efendi; Eka Indriyani MS; Raprayoga, Rusdi Raprayoga (Study of Scientific and Behavioral Management, 2023)
This research examines the influence of financial attitudes and social media on stock investment decisions in Makassar City with risk preferences as a moderating variable. This research uses an associative method with a quantitative approach, a survey using a questionnaire as a data collection tool. The sample in this research is the people of Makassar City who actively use social media and have also invested in shares. The data analysis technique in this research is structural Equation Modelling (SEM) with the help of SmartPLS version 4.0 for Windows. The research results show that financial attitudes and social media have a significant positive influence on stock investment decisions in Makassar City. However, risk preferences cannot moderate the relationship between financial attitudes and social media on investment decisions. This research provides practical and theoretical implications for stock investors and academics in understanding the factors that influence stock investment decisions in the digital era and information that is increasingly easy to access.